2018
DOI: 10.12680/balneo.2018.196
|View full text |Cite
|
Sign up to set email alerts
|

Low-level LASER therapy effects vs. placebo in the treatment of temporo-mandibular joint disorders

Abstract: The purpose of this study was to assess the efficiency of low-level LASER therapy (LLLT) in the treatment of temporomandibular joint (TMJ) pain. LLLT therapy was compared with placebo treatment. Material and methods: A number of 20 patients with TMJ pain were included in this study. The diagnosis was done according to Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). The patients were divided into two groups. The first group received LLLT (660 nm, 90 mW; LaserHF Surgical Unit, Hager & Wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In 2018, a study completed by Buduru et al showed a significant pain reduction and noticed that there is no disadvantage of LLLT. Thus, the author had recommended the use of LLLT for pain reduction in TMD patients [ 30 ]. According to Del Vecchio et al , LLLT can significantly reduce TMD pain symptom, and it is very much effective in TMJD pain management (Del Vecchio et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a study completed by Buduru et al showed a significant pain reduction and noticed that there is no disadvantage of LLLT. Thus, the author had recommended the use of LLLT for pain reduction in TMD patients [ 30 ]. According to Del Vecchio et al , LLLT can significantly reduce TMD pain symptom, and it is very much effective in TMJD pain management (Del Vecchio et al ).…”
Section: Discussionmentioning
confidence: 99%
“…We also indented to identify the impact of this type of therapy on reducing muscle pain in patients suffering from this pathology. Out of the 28 articles included, 9 were metaanalysis, systematic reviews, or literature reviews (3,5,6,25,26,28,29,30,32) and 19 were clinical trial studies (7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,31 ). Therefore, the authors analyzed the articles included in this research and organized the findings based on topic and on answering on some focused questions.…”
Section: Discussionmentioning
confidence: 99%
“…After careful full-text screening and assessment of the risk of bias, 27 RCTs met the inclusion criteria. [7][8][9]11,13,25,[28][29][30][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The selection process and exclusion reasons were presented in the flow chart (Figure 1). These studies, published between 2006 and 2021, included 969 TMD patients consisted of 463(47.78%) for LLLT, 153(15.79%) for TENS, and 353(36.43%) for placebo.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of 969 participants, 546 were women, and 301 were unclear. The search results contained 26 direct comparisons immediately after treatment, [7][8][9]11,13,25,[28][29][30][35][36][37][38][39][40][41][42][43][44][45][46][47][48][50][51][52] in which two were L1 versus placebo, 13 were L2 versus placebo, two were L3 versus placebo, three were TENS versus placebo, one was L1 versus L2, one was L1 versus TENS, one was L2 versus TENS, two were L3 versus TENS, and one was L2 versus TENS versus placebo. Then, the one-month follow-up network contained nine RCTs, 7,9,29,[42][43][44][47][48][49] including seven L2 comparisons with placebo, one L3 comparison with placebo, and one comparison with L2, TENS and placebo.…”
Section: Study Characteristicsmentioning
confidence: 99%